Association between the early repolarization pattern and nocturnal suicide attempts - Hiroshi Kameyama; Kenichi Sugimoto; Fumitoshi Kodaka; Kenji Okuno; Takahiro Masaki; Kazutaka Nukariya; Masahiro Shigeta (Wiley, 2024)
Abstract Aim Numerous recent reports have highlighted the association between mental disorders and electrocardiographic findings. The early repolarization pattern (ERP) on electrocardiogram has been linked with a history of suicide attempts and attention deficit hyperactivity disorder, and associations with impulsivity have also been reported. It is known that suicidal intent is more common at night. Patients who have a mental disorder and ERP may have a higher likelihood of impulsivity, potentially increasing the risk of suicide at night. Methods The subjects were 43 patients with a history of suicide attempts who had undergone electrocardiographic examination at Jikei University School of Medicine Kashiwa Hospital and received intervention from our department. Due to the diurnal variation in electrocardiographic findings, only patients who underwent the examination during the daytime were included. Patients' clinical backgrounds were compared according to the presence or absence of ERP, and the association between nocturnal suicide attempts and ERP was examined using multivariate analysis. Results The frequency of nocturnal suicidal behavior was 76.2% in patients with ERP and 31.8% in those without ERP, but the difference was not significant after Bonferroni correction. In the multivariate analysis, there was a significant association of ERP with nocturnal suicide attempts (p = 0.018). Conclusion The finding of an association between ERP and nocturnal suicide attempts indicates that ERP is a biological indicator that can predict nocturnal suicide attempts.